2017
DOI: 10.1089/hum.2016.184
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of Neurocognitive Deficiency in Mucopolysaccharidosis Type II Mice by Central Nervous System–Directed, AAV9-Mediated Iduronate Sulfatase Gene Transfer

Abstract: Mucopolysaccharidosis type II (MPS II; Hunter syndrome) is a rare X-linked recessive lysosomal disorder caused by defective iduronate-2-sulfatase (IDS), resulting in accumulation of heparan sulfate and dermatan sulfate glycosaminoglycans (GAGs). Enzyme replacement is the only Food and Drug Administration-approved therapy available for MPS II, but it is expensive and does not improve neurologic outcomes in MPS II patients. This study evaluated the effectiveness of adeno-associated virus (AAV) vector encoding hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 37 publications
8
45
0
Order By: Relevance
“…An AAV9 viral vector carrying the IDS gene has been administered to CSF through intracisternal injections in MPS II mice producing, 4 months after treatment, a significant increase in IDS activity throughout the encephalon with a reversal of CNS pathology [166]. The same results were obtained by two subsequent studies [167,168], using a similar strategy, but via intracerebroventricular injections. Laoharawee et al observed supraphysiological levels of IDS in the circulation (160-fold higher than wild-type) for at least 28 weeks post-injection and in most peripheral organs (up to 270-fold) at 10 months post-injection, but only low levels (7% to 40% of wild-type) in all areas of the brain.…”
Section: Adeno-associated Viral Vectorsmentioning
confidence: 62%
See 2 more Smart Citations
“…An AAV9 viral vector carrying the IDS gene has been administered to CSF through intracisternal injections in MPS II mice producing, 4 months after treatment, a significant increase in IDS activity throughout the encephalon with a reversal of CNS pathology [166]. The same results were obtained by two subsequent studies [167,168], using a similar strategy, but via intracerebroventricular injections. Laoharawee et al observed supraphysiological levels of IDS in the circulation (160-fold higher than wild-type) for at least 28 weeks post-injection and in most peripheral organs (up to 270-fold) at 10 months post-injection, but only low levels (7% to 40% of wild-type) in all areas of the brain.…”
Section: Adeno-associated Viral Vectorsmentioning
confidence: 62%
“…Laoharawee et al observed supraphysiological levels of IDS in the circulation (160-fold higher than wild-type) for at least 28 weeks post-injection and in most peripheral organs (up to 270-fold) at 10 months post-injection, but only low levels (7% to 40% of wild-type) in all areas of the brain. Nevertheless, this was enough to prevent brain pathology and neurocognitive impairment [168].…”
Section: Adeno-associated Viral Vectorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In clinics, only the intrathecal delivery of IDS has been investigated [9], while several therapeutic approaches have been tested in the mouse model. These preclinical evaluations include: high systemic dosage of ERT [10], direct administration of IDS to the brain compartment by intracerebroventricular or intrathecal injections [11,12,13], gene therapy mediated by adeno-associated or lentiviral vectors encoding human IDS [14,15,16], substrate reduction therapy [17], and conjugation with brain-targeting ligands [18,19]. In many of these studies, various limitations related to safety or efficacy aspects have been highlighted, while some of them have shown to be more promising and deserving of a deeper analysis.…”
Section: Introductionmentioning
confidence: 99%
“…GAG accumulation in the liver was also reduced, providing further evidence that gene therapy applied directly to the nervous system can cross-correct deficiencies in somatic tissues. Laoharawee et al also evaluated the effectiveness of AAV9 encoding human IDS after intracerebroventricular injection in a MPS II mouse model [89]. Low level of IDS activity in CNS lesions (7–40% of wild-type) was observed; however, GAG accumulation was reduced in brain, and neurologic deficits were improved in treated mice.…”
Section: Pre-clinical Study Of Gene Therapy For Mpsmentioning
confidence: 99%